2016
DOI: 10.1136/gutjnl-2016-312388.560
|View full text |Cite
|
Sign up to set email alerts
|

PTH-157 The Introduction of Biosimilar Infliximab (CT-P13) through A Managed Switching Programme Generates Significant Cost Savings with High Levels of Patient Satisfaction

Abstract: IntroductionBiosimilar infliximab (CT-P5013) has been licensed in the UK for over a year with the potential for significant cost savings, though uptake to-date has been surprisingly slow. We report the introduction of biosimilar infliximab through a closely managed switching programme.MethodsFollowing the licensing of biosimilar infliximab we made a decision to instigate a closely managed switching programme encompassing all patients on maintenance treatment with Remicade and all new starters. A working party … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Additional factors can also have an impact on the costs associated with originator-tobiosimilar NMS. Indeed, three studies reported on the costs, aside from drug costs alone, associated with a switch program, which highlighted patient funding, program implementation, and the additional staff time required as important costing parameters that should not be overlooked [38][39][40]. In British Columbia, the Biosimilar Initiative, which supports originatorto-biosimilar NMS, encourages the reimbursement of various fees billable to the Medical Service Plan, including pharmacist and physician visit fees as well as a fee to fund the nursing staff required to support patients with gastrointestinal diseases [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional factors can also have an impact on the costs associated with originator-tobiosimilar NMS. Indeed, three studies reported on the costs, aside from drug costs alone, associated with a switch program, which highlighted patient funding, program implementation, and the additional staff time required as important costing parameters that should not be overlooked [38][39][40]. In British Columbia, the Biosimilar Initiative, which supports originatorto-biosimilar NMS, encourages the reimbursement of various fees billable to the Medical Service Plan, including pharmacist and physician visit fees as well as a fee to fund the nursing staff required to support patients with gastrointestinal diseases [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that must be considered in the costs associated with originator-to-biosimilar NMS is the establishment of a switch program. Eight studies reported on the costs associated with the implementation of a switch program within their center (Table 1) [38][39][40][41][42][43][44][45]. Four of these studies, namely Razanskaite et al (2017) [44], Shah et al (2018) [43], Chan et al (2019) [41], and Plevris et al (2019) [45], reported substantial savings that were b Fig.…”
Section: Non-medical Switching-related Costsmentioning
confidence: 99%
See 1 more Smart Citation